ANÁLISE DE FATORES DE VIRULÊNCIA RELACIONADOS À ADESÃO E AO FENÓTIPO DE VARIANTE DE PEQUENAS COLÔNIAS EM CEPAS DE Staphylococcus aureus ISOLADAS DE INFECÇÃO ÓSSEA MAXILOFACIAL - Soares, Dalliane Oliveira (2020)
Osteomyelitis is the main infectious disease that affects bone tissue. The most frequent etiologic agent in this type of infection is Staphylococcus aureus, which can be found in the normal microbiota of the skin and mucous membranes in humans, but in fav